Use of solvents and environmental friendly materials for applications in Green Chemistry - Samorì, Chiara <1982> (Alma Mater Studiorum - Università di Bologna, 2010)
The present Thesis studies three alternative solvent groups as sustainable replacement of traditional organic solvents. Some aspects of fluorinated solvents, supercritical fluids and ionic liquids, have been analysed with a critical approach and their effective “greenness” has been evaluated from the points of view of the synthesis, the properties and the applications. In particular, the attention has been put on the environmental and human health issues, evaluating the eco-toxicity, the toxicity and the persistence, to underline that applicability and sustainability are subjects with equal importance.